Self-Empowerment And Coping Strategies In Type 2 Diabetes Mellitus Patients - Kurniyawan, Enggal Hadi; Santoso, Sofi Fitriyah; Widayati, Nur; Dewi, Erti Ikhtiarini; Hakam, Mulia; Deviantony, Fitrio; Fitria, Yeni (Al-Hijrah Indonesia, 2023)
Diabetes Mellitus is a chronic disease that can harm the body, both physically and psychologically (stress). DM patients will carry out adaptive coping strategies to properly manage treatment or therapy. The process of self-empowerment in people with type 2 diabetes mellitus will appear when they have information or knowledge about the disease so that it can influence the patient's self-skills for further treatment. This study aimed to analyze the relationship between self-empowerment and coping strategies in patients with type 2 diabetes mellitus. The design of this study was an analytical observational study using a cross-sectional method. The sampling technique used is consecutive sampling. The sample of this study was type 2 DM patients with 84 respondents. The instrument used in this study is the Diabetes Empowerment Scale-Long (DES-LF) questionnaire and the Cope Inventory questionnaire. Data were analyzed using the Spearman test. Self-empowerment and coping strategies in type 2 diabetes mellitus patients showed close to maximum results. In the results of the study, it was found that there was no significant relationship between self-empowerment and coping strategies in type 2 DM patients with p = 0.086. It means that other factors can influence coping strategies. Health services can educate patients about the importance of coping strategies for DM clients so that they can reduce the impact of DM disease